Remarks on some neotropical Amphibians of the genus Alsodes from Southern Argentina (Anura leptodactylidae) - Cei, José Miguel Alfredo María (1976)
A general review of the genus Alsodes is made, recognizing five Argentine forms. Alsodes gargola neuquensis subsp. nova and Alsodes pehuenche sp. nova are described. It is suggested that Alsodes illotus (Barbour) and Alsodes nodosus (Duméril and Bibron) are identical. The validity of Alsodes verrucosus (Philippi) is also supported.